2018
DOI: 10.1111/echo.14087
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic measures associated with the presence of left ventricular thrombus in patients with chemotherapy‐related cardiac dysfunction

Abstract: In patients with severely reduced LV systolic function due to chemotherapy-induced cardiomyopathy, LV thrombus was found in 7.4% of subjects. Severely decreased LVEF (<20%) and restrictive LV filling pattern were associated with the presence of LV thrombus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…30 Inflammation, hypercoagulability, and endocardial involvement by specific disease processes (eg, amyloidosis, eosinophilic myocarditis) are also important pathophysiological mediators in DCM that may increase the risk of LV thrombus formation. [31][32][33][34][35][36] However, data in relation to specific DCM causes are sparse on both LV thrombus risk and the impact on clinically relevant thrombus/thromboembolism.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Inflammation, hypercoagulability, and endocardial involvement by specific disease processes (eg, amyloidosis, eosinophilic myocarditis) are also important pathophysiological mediators in DCM that may increase the risk of LV thrombus formation. [31][32][33][34][35][36] However, data in relation to specific DCM causes are sparse on both LV thrombus risk and the impact on clinically relevant thrombus/thromboembolism.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
“…8,78 A small number of case reports and case series of LV thrombus have been reported in patients with other forms of DCM, including hypertrophic cardiomyopathy, chemotherapy-related cardiomyopathy, cardiac amyloidosis, cardiomyopathy attributable to Chagas disease, and eosinophilic myocarditis. [31][32][33][34][35] No prospective observational studies or randomized clinical trials have evaluated the impact of anticoagulation in these patients for the primary prevention of LV thrombus.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
“…17 In DCM of autoimmune, toxic, and infectious causes (also known as inflammatory cardiomyopathies), inflammation plays the primary and persistent pathologic role, 18 and several studies have observed a high prevalence of intracardiac thrombus in inflammatory cardiomyopathy populations. 19,20…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective [24] Iodine densities were significantly lower in the LVT than the LV cavity, whereas blood densities in the two areas did not differ significantly Mao, 2018…”
Section: Prevalence and Risk Factorsmentioning
confidence: 96%
“…In a cohort of patients (n=121) with chemotherapyrelated severe LV dysfunction (24), defined as LVEF <30%, the prevalence of LVT was 7.4%. Factors associated with presence of LVT were restrictive filling pattern (OR: 18.13, 95% CI: 4.17-78.89) and LVEF <20% (OR: 36.30, 95% CI: 7.35-179.25).…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%